Prenatal skeletal dysplasia phenotype in severe MLII alpha/beta with novel GNPTAB mutation - Aggarwal, S. (2015)
We report a neonate who was diagnosed as a case of skeletal dysplasia during pregnancy, and was subsequently diagnosed as a case of MLII alpha/beta on the basis of clinical and radiological ﬁndings and molecular testing of the parents. A novel GNPTAB mutation c.1701delC [p.F566LfsX5] was identiﬁed in the father. The case reiterates the severe prenatal phenotype of MLII alpha/beta which mimics skeletal dysplasia and illustrates the utility of molecular genetic analysis in conﬁrmation of diagnosis and subsequent genetic counselling.